Evaluating the creation and understanding of uplift mappings - CROTTI JUNIOR, ADEMAR (My University, 2019)
The majority of data in the Web still resides in other formats than the Resource Description Framework (RDF). RDF is a W3C recommendation for representing information in the Web, facilitating data exchange, data integration and others. One of the main tasks when upgrading legacy systems to the Semantic Web is the conversion of data. The process of converting data in any format into RDF is called uplift. The key stakeholders in this process are web developers, software programmers specialized in the development of systems for the web, and ontology engineers, experts in semantic web technologies such as ontologies, RDF and so on. Several solutions have been proposed, however, these still focus on Semantic Web experts. To facilitate the uplift process and to make the technology available to a wider set of stakeholders, I have developed a method to represent uplift mappings visually. The method draws inspiration from visual programming languages such as Google’s Blockly. Blockly has been used in many projects, such as code.org’s introduction courses. In the visual representation, blocks represent a mapping that automatically generates an uplift mapping. In this experiment, I aim to investigate if such a visual representation: (i) facilitates the creation of accurate uplift mappings; (ii) eases the understandability of uplift mappings; and (iii) imposes an optimal mental workload on users.
SUBMITTED
Keywords: Semantic Web technologies; Resource Description Framework (RDF)